Zachowania kompensujące trudności w komunikacji werbalnej u dzieci z korowymi zaburzeniami mowy (Conversatoria Linguistica, 2019)
The level of development of language, communication and cultural competence ofchildren with speech and language development disorders resulting from structural and/orfunctional changes in brain is insufficient even after many years of regular speech therapy(Grabias, 2001). The article focuses on behavior which all of children with such disorders compensatein communications process for deficiencies in their language skills development. Theresearch material was collected during a logopaedic diagnostic procedure. The basis for analysiswas a test checking individual production of: nouns, verbs and adjectives.